A Comparative Study on Visual Aesthetic Quality and Originality of Children's Book Illustrations: Midjourney Generation vs. Manual Illustrators - Moch Bagoes Pakarti; Tigus Juni Betri (International Journal of Computer and Information System (IJCIS), 2026)
The emergence of Generative AI, such as Midjourney, has sparked significant disruption in the children's book publishing industry by offering efficiency and rapid creation of visual works, while simultaneously raising fundamental debates regarding aesthetic quality and authenticity. This study aims to comparatively evaluate the visual aesthetic quality and originality levels between Midjourney-generated illustrations and those created by manual illustrators. Utilizing an explanatory sequential mixed-methods approach, data were collected through a structured evaluation rubric assessed by a panel of 15 experts (visual communication design academics, children's book editors, professional illustrators, and child psychologists). Quantitative data were analyzed using the Mann-Whitney U test, complemented by descriptive qualitative analysis. Findings reveal that Midjourney excels in technical rendering precision and execution speed, yet exhibits critical flaws in character consistency across story pages and narrative emotional expression. Conversely, manual illustrators scored significantly higher in originality, signature visual style, and narrative visual sensitivity appropriate for children's emotional development. This study concludes that AI cannot currently replace the intuitive role of manual illustrators in producing complete, impactful visual narratives for children's books. The findings imply that publishers should position AI merely as an initial ideation tool while underscoring the necessity of preserving the originality and ethical value of human illustrators' workplease write in English. This document gives formatting instructions for authors preparing papers for publication in the IJCIS. The authors must follow the instructions given in the document for the papers to be published. You can use this document as both an instruction set and as a template into which you can type your own text. Abstract should be no longer than 250 words. It gives a brief summary of the content of the paper and point out the main objective, the methods employed, the results obtained and major conclusions.